Assessment of Nurses’ Knowledge Regarding Oxytocin Administration during Labor at Maternity Hospitals in Al-Kut City - Thamer, Huda; abbas, iqbal (Iraqi National Journal of Nursing Specialties, 2014)
Objectives of the study: To assess nurses knowledge regarding oxytocin administration during labor anddelivery in maternity hospitals, and to find out the relationship between nurses knowledge and studiedvariables (age, level of education, work times (shift) experience year, training course in nursing field).Methodology: Descriptive analytic study was conducted on non-probability sample (convenient) of (70) nursesto assess nurse’s knowledge related to oxytocin administration. The study is conducted at Al- kut Hospital forGynecology Obstetrics and Pediatrics and Al- Zahraa Teaching Hospital during periods 5th February to 24thApril 2013, A questionnaire was used as a tool of data collection to fulfill with objectives of the study andconsisted of three parts, including demographic characteristics (age, level of education, social status, worktimes (shift ), professional characteristics (experience year, license of midwifery practice, Practice midwifery incommunity, In service education, Number training course in nursing field) and nurse’s knowledge related tooxytocin: (Action, Administration of oxytocin , Adverse effect of oxytocin on mother, Adverse effect ofoxytocin on fetus, Side effects, Contraindication and nurse's role in oxytocin administration. Content validityand reliability of the questionnaire were determined through a panel of experts and pilot study. Descriptiveand inferential statistics are used to analyze the data.Results: The results of the study showed that highest percentage (24.3%) were in age group (40-44) years,nursing secondary school graduated, and (30%) of them had (1-5) years of experience in nursing, and (62.9%)was not pass in service education. Their knowledge was adequate in some items and inadequate in certainitems. Regarding oxytocin administration, there were statistical significant association between level ofknowledge and (work time (shift), implementation of ordersRecommendations: Implementation of educational program for nurses about oxytocin administration toincrease their knowledge, further research in this field by using checklist to apply administration technique inright method to prevent error occurrence.